Benzoyl Groups as ortho‐Substituents in Cannabidiol Derivatives: Controlling Axial Conformation about Aryl‐C(sp3) Bonds. Issue 2 (1st June 2018) - Denhez, Clément; Lameiras, Pedro; Flos, Manon; Mirand, Catherine; Berber, Hatice
Abstract : The conformational behaviour arising from the restricted C(sp 2 )–C(sp 3 ) axis in ortho ‐benzoyl‐substituted phenylcyclohexene, phenylcyclohexene oxide and phenylcyclohexane derivatives of cannabidiol was examined by means of VT‐NMR experiments and DFT calculations. In the case of epoxide and phenylcyclohexane derivatives, the compounds are atropisomeric with barriers slightly lower than 90 kJ mol –1 at 298 K. Transition states for the interconversion of the conformers were located, and particularly in phenylcyclohexanes, different intermediate cyclohexane conformations are involved to allow free rotation around the pivot bond. The structure of the favoured ( P ) phenylcyclohexane conformer was also established by X‐ray diffraction. The conformational control induced by the presence of the benzoyl group is mainly governed by intramolecular stabilizing π–π and CH–π interactions according to the natural bond orbital (NBO) analysis. Abstract : O ‐benzoyl ortho ‐substituted cannabidiol derivatives phenylcyclohexene, phenylcyclohexene oxide and phenylcyclohexane were synthesized. Their conformational behaviour around the pivot bond (phenyl‐C3) was analysed in detail by combined XRD, VT‐NMR experiments and DFT calculations.